Dear Professor: A Chronicle of Absences - Noterdaeme, Filip (punctum books, 2016)
Dear Professor: A Chronicle of Absences is a collection of over two hundred often involuntarily comical emails in which students excuse themselves for missing class. The result is a satirical yet unexpectedly sympathetic collective portrait of modern-day academia where both students and teachers feel pressured to comply with the impositions of hyper-connectivity.